pengaruh pengembangan karir dan motivasi kerja terhadap kinerja pegawai pada kantor sistem administrasi manunggal satu atap (samsat) kabupaten sidenreng rappang - Gusna Gaffar; fadlina fadlina; suriadi suriadi (Paser Institute Management and Busines, 2025)
Abstract: This research aims to find out how much influence career development (X1) and work motivation (X2) have on employee performance (Y) at the one roof single administration system (SAMSAT) office in Sidenreng Rappang regency, using kuantitative methods, data collection methods through observation, interviews, kuestionnaires and documentation to obtain data from the office. The research results show that partially career development (X1) has a negative and insignificant effect on employee performance (Y) at the one roof single administration system (SAMSAT) office in Sidenreng Rappang district with a significance value of 0,130 (1,3%). Partially, work motivation (X2) has a positive and significant effect on enployee performance (Y) at the one roof single administration system (SAMSAT) office in Sidenreng Rappang district with a significance value of 0,000 (0,0%). Simultaneously career development (X1) and work motivation (X2) have a positive and significant effect on employee performance (Y) at the one roof single administration system (SAMSAT) office in Sidenreng Rappang district with a significance value of 0,000 (0,0%). Keywords: Career Development, Work Motivation, Employee Performance